Development of cephalometric radiography in orthodontic imaging: a literature review - Prativi, Shinta Amini; Suksmono, Andriyan Bayu; Mengko, Tati Latifah; Danudirdjo, Donny (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: This review article aims to discuss the development of lateral cephalometric radiography use in science until now. Review: The search for studies on the identification of lateral cephalometric anatomical landmarks based on artificial intelligence was conducted by involving four databases: PubMed, IEEE Xplore, Google Scholar, and Scopus. The article selection was conducted using the keywords "Cephalometric Radiograph," "Automatic Cephalometric," "Cephalometric Landmarking," and "Cephalometric Digital" from January 2000 to March 2022. A total of 11 articles were obtained for this study. Cephalometric radiography is a radiographic technique that shows a picture of the skull and is widely used in dentistry to analyze and assess the relationship between teeth, jaws, and facial bones. Cephalometric analysis can be done by identifying anatomical landmark points and measuring angles on lateral cephalometric radiographs. The development of cephalometric radiography in biomedical imaging, especially in terms of the processing of cephalometric radiograph images from the process of forming X-rays to their potential use in the process of determining automatic anatomical landmark points. Conclusion: The results of the literature review of the development of dental radiology, especially digital cephalometric radiography, continue to increase, and its development is supported by computing technology, especially Artificial Intelligence. Keywords: Lateral cephalometric; biomedical imaging; artificial intelligence